Controlled formation of closed-edge nanopores in graphene. Issue 27 (19th June 2015) - He, Kuang; Robertson, Alex W.; Gong, Chuncheng; Allen, Christopher S.; Xu, Qiang; Zandbergen, Henny; Grossman, Jeffrey C.; Kirkland, Angus I.; Warner, Jamie H.
Abstract : Dangling bonds at the edge of a nanopore in monolayer graphene make it susceptible to back-filling at low temperatures from atmospheric hydrocarbons, leading to potential instability for nanopore applications, such as DNA sequencing. Abstract : Dangling bonds at the edge of a nanopore in monolayer graphene make it susceptible to back-filling at low temperatures from atmospheric hydrocarbons, leading to potential instability for nanopore applications, such as DNA sequencing. We show that closed edge nanopores in bilayer graphene are robust to back-filling under atmospheric conditions for days. A controlled method for closed edge nanopore formation starting from monolayer graphene is reported using an in situ heating holder and electron beam irradiation within an aberration-corrected transmission electron microscopy. Tailoring of closed-edge nanopore sizes is demonstrated from 1.4–7.4 nm. These results should provide mechanisms for improving the stability of nanopores in graphene for a wide range of applications involving mass transport.